Differential welfare state impacts for frontier working age families - Irina S. Burlacu; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2012)
Benefits and taxes vary greatly across the European Union owing to incongruent welfare and taxation systems. This paper analyzes how welfare states achieve insurance and equity objectives for residents who work in other countries. The aim is to evaluate the impact of unemployment benefits and income taxation on these frontier workers' welfare in Luxembourg and Belgium that exhibit similar welfare state objectives. The analysis is based on social security coordination Regulation 883/2004 provisions on unemployment, taxation regimes and bi-lateral tax treaties. We find mixed results. First, while countries follow analogous welfare regimes and pursue similar welfare objectives, their ensuing outputs differ significantly. Second, differences in unemployment conditions and benefits favor high discrepancies in residents' incomes. Third, mobility creates high vertical and horizontal inequity among Belgian and Luxembourgish residents.
Keywords: I38; 330; frontier workers; social policy; policy coordination; Internationale Arbeitsmobilität; Grenzgebiet; Arbeitslosenversicherung; Einkommensteuer; Sozialstaat; Wirkungsanalyse; Belgien; Luxemburg